2013
DOI: 10.5021/ad.2013.25.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Altered Levels of Sphingosine and Sphinganine in Psoriatic Epidermis

Abstract: BackgroundCeramides are the main lipid component of the stratum corneum and are a structurally heterogeneous and complex group of sphingolipids of which sphingoid bases are the basic structural constituents. Altered levels of sphingoid bases have been reported in skin conditions that involve dryness and barrier disruption, including atopic dermatitis.ObjectiveThe purpose of this study was to investigate the altered levels of sphingoid bases in psoriatic epidermis and their relationship with the clinical severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
3
24
0
1
Order By: Relevance
“…Even though there are no data available on increased ceramidase activity in psoriatic patients, Moon et al [35] described a highly significant positive correlation between the % change of ceramidase activity in the lesional skin of psoriatic patients and PASI score.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are no data available on increased ceramidase activity in psoriatic patients, Moon et al [35] described a highly significant positive correlation between the % change of ceramidase activity in the lesional skin of psoriatic patients and PASI score.…”
Section: Discussionmentioning
confidence: 99%
“…Z kolei S1P jest antagonistą ceramidów, reguluje odpowiedź immunologiczną i angiogenezę [21,22]. Wykazano zmniejszoną ilość CER w skórze zmienionej łuszczycowo w porównaniu z niezajętą chorobą oraz zwiększoną ilość sfingozyny, prekursora S1P [23,24]. U myszy pozbawionych enzymu palmitoilotransferazy serynowej (serine palmitoyltransferase -SPT), biorącego udział w syntezie CER, wystąpiły zmiany łuszczy-copodobne potwierdzone histopatologicznie [25].…”
Section: Serum Lipids Cholesterols Triglycerides and Apolipoproteinsunclassified
“…S1P is an antagonist of ceramides, regulating immune response and angiogenesis [21,22]. A reduced amount of CER in psoriatic skin, compared to unaffected skin, and an increased amount of sphingosine, a precursor of S1P, have been demonstrated [23,24]. Mice deficient in serine palmitoyltransferase (SPT) enzyme involved in CER synthesis, have been found to develop histopathologically verified psoriasis-like lesions [25].…”
Section: Lipidy W Naskórkumentioning
confidence: 99%
“…Not only the ceramide profiles but also the levels of sphingoid bases were changed in the psoriatic epidermis. Sung and colleagues reported that levels of sphingosine and sphinganine were increased in the psoriatic epidermis and increased expression of ceramidase was positively correlated with the clinical severity of psoriasis[9]. These studies suggest that the alteration of SC lipids could, at least partially, be linked to the decreased skin barrier function in the skin of psoriasis patients.…”
Section: Lipidomics In Skin Diseasesmentioning
confidence: 99%